Oral Delivered Dexmedetomidine Promotes and Consolidates Non-rapid Eye Movement Sleep via Sleep–Wake Regulation Systems in Mice - Feng, Zhen-Xin; Dong, Hui; Qu, Wei-Min; Zhang, Wei (Frontiers in Pharmacology, 2018)
Dexmedetomidine, a highly selective α2-adrenergic agonist, is widely used in clinical anesthesia and ICU sedation. Recent studies have found that dexmedetomidine-induced sedation resembles the recovery sleep that follows sleep deprivation, but whether orally delivered dexmedetomidine can be a candidate for the treatment of insomnia remains unclear. In this study, we estimated the sedative effects of orally delivered dexmedetomidine by spontaneous locomotor activity (LMA), and then evaluated the hypnotic effects of dexmedetomidine on sleep-wake profiles during the dark and light phase using electroencephalography/electromyogram (EEG/EMG), respectively. Using c-Fos staining, we explored the effects of dexmedetomidine on the cerebral cortex and the sub-cortical sleep-wake regulation systems. The results showed that orally delivered dexmedetomidine at 2 hours into the dark cycle reduced LMA and wakefulness in a dose-dependent manner, which was consistent with the increase in non-rapid eye movement sleep (NREM sleep). However, dexmedetomidine also induced a rebound in LMA, wake and rapid eye movement sleep (REM sleep) in the later stage. In addition, orally delivered dexmedetomidine 100 μg/kg at 2 hours into the light cycle shortened the latency to NREM sleep and increased the duration of NREM sleep for 6 hours, while decreased REM sleep for 6 hours. Sleep architecture analysis showed that dexmedetomidine stabilized the sleep structure during the light phase by decreasing sleep-wake transition and increasing long-term NREM sleep (durations of 1024–2024 s and >2024 s) while reducing short-term wakefulness (duration of 4–16 s). Unlike the classic hypnotic diazepam, dexmedetomidine also increased the delta power in the EEG spectra of NREM sleep, especially at the frequency of 1.75–3.25 Hz, while ranges of 0.5–1.0 Hz were decreased. Immunohistochemical analysis showed that orally delivered dexmedetomidine 100 μg/kg at 2 hours into the dark cycle decreased c-Fos expression in the cerebral cortex and sub-cortical arousal systems, while it increased c-Fos expression in the neurons of the ventrolateral preoptic nucleus. These results indicate that orally delivered dexmedetomidine can introduce sedative and hypnotic effects by exciting the sleep-promoting nucleus and inhibiting the wake-promoting areas.